Western plainchant: a handbook - Hiley, David (Oxford Clarendon Press, 1993)
Plainchant is the oldest substantial body of music that has been preserved in any shape or form. It was first written down in Western Europe in the eighth to ninth centuries. Many thousands of chants have been sung at different times or places in a multitude of forms and styles, responding to the differing needs of the church through the ages. This book provides a clear and concise introduction, designed both for those to whom the subject is new and those who require a reference work for advanced study. It begins with an explanation of the liturgies that plainchant was designed to serve. It describes all the chief genres of chant, different types of liturgical book, and plainchant notations. After an exposition of early medieval theoretical writing on plainchant, Hiley provides a historical survey that traces the constantly changing nature of the repertory. He also discusses important musicians and centers of composition. Copiously illustrated with over 200 musical examples, this book highlights the diversity of practice and richness of the chant repertory in the Middle Ages. It will be an indispensable introduction and reference source on this important music for many years to come.